2017
DOI: 10.1080/09614524.2017.1359236
|View full text |Cite
|
Sign up to set email alerts
|

Access and coverage: which farmers do plant clinics reach in Uganda?

Abstract: This article reports on a study that assessed farmers' access to, and coverage of, five plant clinics operating from market places in two districts of Uganda. Despite the noticeable geographic and thematic coverage of the services, placing plant clinics at markets did not automatically ensure equitable access and high farmer attendance. Clinic users were predominantly middle-aged male farmers and overall attendance was relatively low. Uganda has taken plant clinics to scale in recent years due to their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…Where repeat plant clinic visits were common despite the long distance, further studies may be needed to assess what the optimal clinic distribution would be. While some studies have shown a higher male to female ratio among plant clinic users (Karubanga et al, 2017), this study shows that men were less likely to participate at plant clinics compared to women. This implies that plant clinics are responsive to farmer needs irrespective of gender, although participation may be constrained by institutional or socio-cultural impediments, similar to studies by Achandi et al (2018).…”
Section: Discussioncontrasting
confidence: 73%
“…Where repeat plant clinic visits were common despite the long distance, further studies may be needed to assess what the optimal clinic distribution would be. While some studies have shown a higher male to female ratio among plant clinic users (Karubanga et al, 2017), this study shows that men were less likely to participate at plant clinics compared to women. This implies that plant clinics are responsive to farmer needs irrespective of gender, although participation may be constrained by institutional or socio-cultural impediments, similar to studies by Achandi et al (2018).…”
Section: Discussioncontrasting
confidence: 73%
“…The results imply that policy interventions that encourage the establishment of and farmers’ participation in plant clinics can contribute to global efforts to achieve a zero‐hunger world by 2030. Given that our results and those of previous studies (e.g., Karubanga, 2017; Majuga et al ., 2018) have shown that physical distance and lack of awareness are among the key barriers to plant clinic participation, efforts to expand the reach of plant clinics could include better publicity (through, for instance, linkages with other extension activities such as farmer field schools); the rotation of plant clinics between different communities (i.e., mobile plant clinics); and building the capacity of extension workers in plant health diagnostics and advice. Moreover, our results suggest that strategies aimed at improving women’s access to plant clinic services may lead to greater food security gains.…”
Section: Resultssupporting
confidence: 88%
“…Good plant health is fundamental to ensure food and income security among smallholder farmers, so as to meet the demands of local and global markets (Danielsen et al 2013). Likewise, effective plant healthcare is essential for producing healthy crops for both human and animal consumption (Karubanga, Matsiko, and Danielsen 2017), as well as for non-food purposes (Danielsen et al 2012). However, substantial amounts of crop produce are lost every year due to plant health problems (Karubanga, Matsiko, and Danielsen 2017).…”
Section: Introductionmentioning
confidence: 99%